Marriage Delayed or Marriage Forgone? New Cohort Forecasts of First Marriage for U.S. Women - Goldstein, Joshua R.; Kenney, Catherine T. (American Sociological Review, 2001)
Do recent declines in first marriage rates signal that an increasing proportion of women will remain single their entire lives, or merely that they are postponing marriage to older ages? Our forecasts for cohorts born in the 1950s and 1960s suggest that marriage will remain nearly universal for American women—close to 90 percent of women are predicted to marry. However, separate forecasts by educational attainment reveal a new socioeconomic pattern of first marriage: Whereas in the past, women with more education were less likely to marry, recent college graduates are now forecast to marry at higher levels despite their later entry into first marriage. This educational crossover, which occurs for both black women and white women in recent cohorts, suggests that marriage is increasingly becoming a province of the most educated, a trend that may become a new source of inequality for future generations. Forecasts presented here use data from the 1995 Current Population Survey and compare estimates from the Hemes model with those from the Coale-McNeil model.